Smart temperature monitoring system for parabolic solar thermal collector integrated with membrane distillation system - Nadzirah, Mohd Mokhtar; Nornabila, Abu; F. N., Zaibuddin; Yi, L. K.; Mohd. Amirul Hilmi, Mohd Hanoin; Nor Amirah Safiah, Muhamad; Amir, Abdul Razak; Muhamad Sukri, Hadi (Institute of Electrical and Electronics Engineers Inc., 2020)
In this work, a smart temperature monitoring system was developed for a Parabolic Solar Thermal Collector (PSTC) integrated with Membrane Distillation (MD) system. The objectives of this work were to monitor and record the temperature data of salt solution in the PSTC system and to control the circulating water pump flow based on the targeted temperature. The PSTC system was used as a supporting system to pre-heat the salt solution until the it reaches the desired temperature. This was monitored by a DS18B20 waterproof temperature sensor. The real-time data was then be displayed on an LCD, saved in a microSD card and via smart phone. An Internet of Thing (IoT) of Blynk Applications and data logging systems were utilized. The energy and the separation performance of the integrated system was also investigated. The highest temperature attained by the PSTC system based on the conducted experiments was above 60°C. Based on the results, a fluctuation of energy consumption by the integrated system was observed. This was due to the supplementary energy supplied by the solar collector system. The integrated system also exhibited a moderate separation efficiency with maximum permeate flux of 3.5083 kg/m2.h and salt rejection of 93.96%. As a conclusion, the PSTC system integrated with MD system can surely bring a lot of benefits for the desalination industry. Additionally, IoT can be employed in the future as means to accurately monitor solution temperature for such integrated systems.